INOVASI LAYANAN PERCEPAT PENERBITAN DOKUMEN KEPENDUDUKAN BAGI PENGUNGSI DI KOTA PEKANBARU - Fitri Diana; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Service innovation provided by the Regional Government through the Population and Civil Registration Service are breakthroughts in public services which are creative idea and modification that are able to provide benefits to the community. Through Disdukcapil, the government provides population administration services in recording e-KTP to the public. One of the Disdukcapil that provides population administration services is Pekanbaru City Disdukcapil through the Sipintar Innovation (Service System to Complete the Identity of Displaced Persons). The purpose of this study was to determine the implementation of Sipintar innovation in Pekanbaru City Disdukcapil and identify factors that hinder the implementation of Sipintar innovation. This research uses bugge's theory of innovation success attributes in Winda (2021), where there are six indicators, namely: Governance and Innovation, Sources of the Ideas for Innovation, Innovation Culture, Capabilities and Tools, Objectives, Outcomes, Expense and Obstacles, Collecting Innovation Data for Single Innovation. This type of research is qualitative research with a phenomenological approach. The collection of necessary data, both primary and secondary data, is collected through interviews, observations, documentation, then analyzed so that conclusions can be drawn from existing research problems. The result of this study is that the existing innovations have not been optimally implemented because there are still inhibiting factors in its implementation, namely the low socialization of face-to-face / direct innovations, the limitations of e-KTP recording devices, and also network disruptions when recording e-KTP. Keywords: Service Innovation, Population Documents, Displaced Persons